<span>-6x - 2 = 40
-6x = 42
x = -7
..................</span>
Answer: m² + 3m - 10 = 0
Step-by-step explanation:
From the expression, considering
6x + 5 = m
The original expression
( 6x + 5 )² - 10 = -18 - 15
Factorize the right hand expression,
-18 - 15 = -3( 6x - 15 )
Since m = 6x + 5 , we now substitute for m in that expression
m² - 10 = -3m
Now re arrange the equation in the form,
ax² - bx + c = 0
Now back to the equation,
m² + 3m - 10 = 0,
So the equivalent equation will be
m² + 3m - 10 = 0
Option B: (b-a)/(b+a) is the correct answer
Step-by-step explanation:
The given expression is;
![\frac{\frac{1}{b}-\frac{1}{a}}{\frac{1}{b}+\frac{1}{a}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B1%7D%7Bb%7D-%5Cfrac%7B1%7D%7Ba%7D%7D%7B%5Cfrac%7B1%7D%7Bb%7D%2B%5Cfrac%7B1%7D%7Ba%7D%7D)
First of all we have to take LCM in both numerator and denominator
So,
![=\frac{\frac{b-a}{ab}}{\frac{b+a}{ab}}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%5Cfrac%7Bb-a%7D%7Bab%7D%7D%7B%5Cfrac%7Bb%2Ba%7D%7Bab%7D%7D)
The reciprocal of the denominator will be multiplied with the numerator for simplification
So,
![=\frac{b-a}{ab} * \frac{ab}{b+a}\\= \frac{b-a}{b+a}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bb-a%7D%7Bab%7D%20%2A%20%5Cfrac%7Bab%7D%7Bb%2Ba%7D%5C%5C%3D%20%5Cfrac%7Bb-a%7D%7Bb%2Ba%7D)
Hence,
Option B: (b-a)/(b+a) is the correct answer
Keywords: Fractions, expressions
Learn more about fractions at:
#LearnwithBrainly
Answer:hi i no get math but i hope you get a answer soon :)
Step-by-step explanation:
After thorough research, there exists the same question that ask:
<span>Based on the equation, how much more money, in millions of dollars, was earned in revenue for week 3 than for week 5?</span>
The question will give a high value but nevertheless, it is still answerable.
Function is equal to 73^x
For 3 weeks , we will get
= 73^3 - 73^2
For 5th week = 73^4 x 72
Based on the equation, it is obvious that we get more in 5th week compared to 3rd of around 2 billion.